Mengatasi Stres dengan Pendekatan Logoterapi untuk Meningkatkan Spiritualitas Lansia di BSLU Mandalika NTB (Jurnal Bimbingan dan Konseling Islam, 2020)
This study aims to deal with stress with a logotherapy approach in improving the spirituality of the elderly at BSLU Mandalika NTB and to find out the obstacles in overcoming stress with a logotherapy approach to improve the spirituality of the elderly at BSLU Mandalika NTB. The method used is descriptive qualitative research with a case study approach. The results of logotherapy research using reflective paradoxical intention techniques and spiritual guidance are effective in overcoming stress in the elderly at BSLU Mandalika NTB. The obstacles experienced in the implementation of logotherapy are caused by several factors, including the difficulty of communicating with the elderly and the physical condition of the elderly who cannot take long in conducting interviews, and the last one because of past trauma which is still difficult to forget.